Cooperation and Conflict Within the Microbiota and Their Effects On Animal Hosts - Figueiredo, Alexandre R. T.; Kramer, Jos (Frontiers in Ecology and Evolution, 2020)
Symbioses between animals and microbes are ubiquitous, and often have drastic fitness effects on both parties. A rapidly growing body of research now shows that many of these effects are driven by social interactions among the symbionts. For instance, microbes frequently cooperate by producing shareable ‘public goods’ that can mediate both virulence and host-beneficial functions. Conversely, hosts often exert control over symbionts by targeting their social interactions. Despite this pivotal role, we have only started to uncover the full diversity of microbial interactions, and many of the factors that shape variation in their effects on host function and evolution across different symbioses remain elusive. Here, we (i) review the known diversity of microbial interactions across different symbioses, and (ii) argue that variation in their nature and impact is often determined by differences in symbiont diversity. In particular, we first give a primer on the social lives of microbes, and then discuss how intraspecific and interspecific interactions among microbial symbionts affect – and are affected by – their host. Subsequently, we move to the evolution of symbiosis, and discuss the role of microbial interactions in symbioses that feature only few versus many different symbiont species. We show that symbiont-rich symbioses are shaped by strong interspecific competition, which selects against many host-beneficial forms of microbial cooperation, and thereby limits the scope for the evolution of strong host-symbiont dependencies. Conversely, symbioses involving only few symbiont species are often characterized by forms of microbial cooperation that mediate host-beneficial services, a situation that increases the scope for the evolution of host-symbiont dependencies. Overall, we infer that the explicit consideration of social dynamics within symbiont communities of varying complexity is crucial to advance our understanding of how microbes shape animal function and evolution.